Influence of Glycyrrhiza glabra Extract on Growth, Gene Expression of Gut Integrity, and Campylobacter jejuni Colonization in Broiler Chickens - Ibrahim, Doaa; Sewid, Alaa H.; Arisha, Ahmed H.; abd El-fattah, Amir H.; Abdelaziz, Adel M.; Al-Jabr, Omar A.; Kishawy, Asmaa T. Y. (Frontiers in Veterinary Science, 2020)
Phytogenic feed additives have been gaining considerable interest due to their ability to improve gut health and thereby performance of broiler chickens. The impact of Glycyrrhiza glabra (licorice) extract (GE) on expression of genes coding for tight junction proteins and gut protection and Campylobacter jejuni colonization in broilers has not been discussed until now. Thus, the current study assessed the effective dose of GE for maximum growth in broiler chickens, clear-cut molecular mechanisms related to integrity and health of intestine, and controlling C. jejuni colonization. Over a 35-day feeding period, a total of 500 Ross broiler chicks were allocated to five groups; the first group was fed a control diet without GE and the second group to the fifth group were fed a control diet with GE (0.25, 0.5, 1, and 2 g/kg of diet); each group comprised 100 chicks with 10 replicates (10 birds/replicate). Birds fed GE had an improved body weight gain and feed conversion ratio. Furthermore, the highest body weight gain was observed in the group that received 1 g/kg of GE (P < 0.05). The expression of genes coding for tight junction proteins [occludin and junctional adhesion molecules (JAM)] was upregulated in all groups supplemented with GE. Moreover, birds fed 1 g/kg of GE exhibited the maximum gene expression of occludin and JAM [0.2 and 0.3 fold change, respectively (P < 0.05)]. In relation to enterocyte protective genes [glucagon-like peptide (GLP-2) and fatty acid-binding protein (FABP-6)], use of GE significantly upregulated expression of GLP-2 gene with 0.8 fold change in 2 g/kg of the GE supplemented group (P < 0.05) while the expression of FABP-6 gene was not affected by GE supplementation (P > 0.05). After challenge with C. jejuni, the expression of mucin (MUC-2) gene was upregulated and the inflammatory markers such as Toll-like receptors (TLR-4) and interleukin (IL-1β) were downregulated with increasing level of supplemented GE (P < 0.05). The mean log10 count of C. jejuni in cecal samples after 7 days post-infection by culture and real-time qPCR was decreased in groups fed GE in a dose-dependent manner (P < 0.05). In addition, the highest reduction of C. jejuni count in cecal samples by culture and real-time qPCR was observed in the group fed 2 g/kg of GE (2.58 and 2.28 log10 CFU/g, respectively). Results from this study suggested that G. glabra extract (1 g/kg) improved growth performance of broiler chickens, as well as influenced the maintenance of intestinal integrity and reduced C. jejuni shedding from infected birds.